CULTURE-BASED DIFFERENCES IN CONCEPTUAL METAPHORS ACROSS LANGUAGES (Živi jezici: Journal for Foreign Languages and Literatures, 2021)
The ever-evolving study of conceptual metaphors shed a new light on this phenomenon and the importance of culture in creating meaning. It entrenched the emergence of new disciplines, including cultural linguistics. The goal of this paper is to present a brief overview of some work about cultural conceptualizations in different languages. We will try to show how culture impacts the creation of meaning and what may be the advantages of the cultural linguistic account, but also what may be misleading in this kind of research. Vast material is reduced to examples which include conceptualizations of body, time, feelings, and image schemas. Aside from these, there is also a part dedicated to cultural differences that occur depending on the context of communication. Our concise analysis leads to the conclusion that, just as seeing conceptual metaphor exclusively as a physiological phenomenon, considering only cultural factors may be equally biased. Taking into account the interplay between multiple factors can give more precise overall picture.
Keywords: conceptual metaphor; cultural linguistics; cognitive linguistics; cultural metaphor; embodiment; culture